PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN DENGAN FAMILY MANAGEMENT SEBAGAI VARIABEL MODERASI - Bernadet Liesiana Laurenty; Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims at how the effect of tax avoidance on firm value, and the moderating effect of family management toward the relationship of tax avoidance and firm value listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 380 data. Data processing techniques using multiple regression analysis what helped by Eviews version 10. The results of this study indicate that tax avoidance have a positive and significant effect on firm value, but family management has no moderating effect on the relationship of tax avoidance and firm value. The implication of this study is the need to increase the performance of the company’s management carrying out the tax avoidance activities in order to maximize company’s profits wich will provide a good signal for investors, thereby increasing firm value.